Uji potensi ekstrak etanol daun gewang (Corypha utan lamk) sebagai antihelmintik terhadap cacing Ascaris suum secara in vitro - Trianto Umbu Reku; Nemay A. Ndaong; Julianty Almet (Jurnal Veteriner Nusantara, 2019)
The system of pig farm in East Nusa Tenggara (NTT) province is a traditional farm so that pigs are susceptible to diseases caused by endoparasite. Parasite species commonly invested in pigs is Ascaris suum. Treatment used and believed to have an effect as anti-endoparasite for infected pigs is leaves of Gewang (Corypha utan Lamk). The aims of this study were to assess the potency of ethanol leaves extract of gewang against worm Ascaris suum in vitro and to know the potential compound in the leaves by phytochemical test. Samples of 60 Ascaris suum were collected from small intestines of pigs. Extract was obtained by evaporation and maceration methods, and then divided into several concentrations, which were 5%, 10% and 15%. Control group used physiological saline 0.9%. The results showed that the 15% extract had the fastest time (21.33 hours) to kill the parasite, while the 10% and 5% extract needed 28.33 and 42.33 hours respectively. Based on phytochemical test, the extract contained saponins and tannins. The conclusion of this study is that the extract of ethanol leaves of Gewang has good potential as anthelmintic for Ascaris suum.